Nature Environment Representation in Raudal Tanjung Banua Poetries: Exocriticism Review (Universitas Negeri Semarang, 2018)
Raudal Tanjung Banua’poems is containing many problems of the nature environment. This study aims to analyze the representation of the nature environment in Banua’s poems and the reasons for the emergence of environmental problems in the poem. The approach of this research is ecocriticism and semiotic approach. Heuristic method is used to collecting data and hermeneutic method is used analysis the data. The results of the analysis show that environmental representations in Banua poetry can be grouped into four categories, namely the occurrence of exploitation of nature, the occurrence of nature environment damage, the causes of damage to the nature environment, and the benefits of the nature environment for humans. The appearance of nature environment problems in Banua’s poem is motivated by several reasons, among others, because Banua can not directly protest, because of his love for the nature environment, as his prayer that the nature environment can be in good condition, hope for a better life for fishermen and farmers, and the form of a devotee to God. The results of this study are expected to provide benefits for solving environmental problems and the development of environmentally sound literature.